(untitled) - Tubbs, Jeffrey S. (Hoboken, N.J., 2007)
The architect's primary source for information on designing for egress, evacuation, and life safety, Egress Design Solutions, Emergency Evacuation and Crowd Management Planning, is written by proven experts on egress issues. Meacham and Tubbs are engineers with Arup, an international firm with a stellar reputation for quality design and engineering. Their book examines egress solutions in terms of both prescriptive and performance-based code issues. A portion of the book focuses on techniques for providing egress design solutions and for coordinating egress systems with other critical life safety systems. Another part reviews historic and recent tragic life-loss fire events. As such, this is easily the most comprehensive take on the subject, written especially for architects
Keywords: Fire escapes,Buildings,Building layout,Crowd control,Thoát khỏi đám cháy,Kiểm soát đám đông,Tòa Nhà; Evacuation,Sơ Tán